1974
DOI: 10.1128/jb.117.2.422-431.1974
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Mediated Alteration of theMicrosporum gypseumGermination Protease Specificity for Substrate: Enhanced Keratinase Activity

Abstract: Inorganic phosphate was found to decrease the caseinolytic and ethyl-esterase activities of the Microsporum gypseum germination protease. The germination protease possessed exokeratinase (beta-keratinase) activity immediately after release from the fungal spore. After phosphate treatment of the enzyme, the germination protease also possessed endo-keratinase (alpha-keratinase) activity. Phosphate altered the protease's pH optimum from 9.0 to 7.0 and decreased the molecular weight from 33,000 to 16,000. These va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The data comparable with our results are still sporadical in the literature. Page & Stock [29] studied a protease from M . gypseum macroconidia and recorded a 129-up to 790-fold increase in 'keratinase' activity in the presence of millimolar concentrations of sulphite, cysteine and dithiothreitol.…”
Section: Discussionmentioning
confidence: 99%
“…The data comparable with our results are still sporadical in the literature. Page & Stock [29] studied a protease from M . gypseum macroconidia and recorded a 129-up to 790-fold increase in 'keratinase' activity in the presence of millimolar concentrations of sulphite, cysteine and dithiothreitol.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of proteolytic enzymes in preparations from different dermatophytes and other pathogenic fungi have been reported by various workers. [16][17][18][19][20][21][22][23][24][25][26][27][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] While it has been suggested that strain differences reflect differences in proteolytic activities of pathogenic fungi, we know of no studies comparable with ours which demonstrate fundamental homologies in the proteolytic systems of different strains within a single taxon, although the proteases they produce may have adaptive specificities related to the substrates and the tissues that they invade. The homologies in the quantitative composition of proteases of two isolates of M. gypseum emerging from the same ecological group (soil) in this study are explicable in epidemiological terms corresponding to reported multifold protease interstrain variability between clinical and environmental isolates of Microsporum canis and Aspergillus niger.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the proximity of M. gypseum to superficial dermis layers, skin was the substrate of choice not employed in most of the previous studies on dermatophyte keratinolytic activity determinations. [24][25][26][27]31,32 Degradation of buffalo skin by M. gypseum cultures was connected with the synthesis of proteolytic enzymes released extracellularly. Another noteworthy index for measuring M. gypseum keratinolytic activity appeared to be gravitationally measurable loss of keratin substrate coupled with mycelial yield (biomass) of the fungus at the expense of degraded products released into the medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations